Casting a long shadow: Exploring the link between childhood maltreatment and cancer in adulthood - Matthew Robert Langiano; Carmine Malfitano; Esme Fuller-Thomson (PLoS ONE, 2026)
Childhood adversities, including physical abuse, sexual abuse, and exposure to parental domestic violence (PDV), have been linked to negative health outcomes in adulthood, yet their specific association with cancer in older Canadians remains understudied. The current study investigated the associations between these specific childhood adversities and cancer in Canadian older adults. We conducted a secondary analysis of the nationally representative cross-sectional 2022 Canadian Mental Health and Access to Care Survey (MHACS). The sample size was 2,636 Canadians aged 65 and older. Bivariate and logistic regression models assessed the relationship between self-reported cancer diagnoses and self-reported childhood adversities – childhood sexual abuse (CSA) (including unwanted touch/fondling and Childhood Sexual Violence with Coercion (CSVC)), childhood physical abuse (CPA), and PDV. Logistic regression analyses controlled for demographic characteristics, socioeconomic status, health behaviors, chronic pain, mental health conditions, and psychosocial factors. In the bivariate analyses, those who had experienced childhood adversities had a significantly (p < 0.05) higher prevalence of cancer than those who had not (CPA 28% vs. 20.7%; PDV 26.5% vs. 20.6%; CSVC 35.5%; unwanted touch/fondling 25.5%, no CSA 20%). After comprehensive adjustment for demographic, socioeconomic, behavioral, and psychosocial factors, CSVC was associated with double the odds of cancer diagnosis (odds ratio = 2.05; 95% confidence interval 1.41–2.98), but the other forms of childhood adversity no longer reached statistical significance. Childhood adversities are associated with an elevated prevalence of cancer in later life, and the association between CSVC and cancer remained significant even after adjustments for most of the known risk factors for cancer. Further longitudinal research exploring stress-induced biological changes and immune dysregulation is needed among those with a history of childhood adversities. These findings lend support to the integration of trauma-informed care into oncology services.